Trajectories in glycated hemoglobin and body mass index in children and adolescents with diabetes using the common data model - Yun Jeong Lee (Nature Portfolio, 2021)
Abstract We evaluated trajectories of glycated hemoglobin (HbA1c) levels and body mass index z-scores (BMIz) for 5 years after diagnosis among Korean children and adolescents with type 1 diabetes (T1D) or type 2 diabetes (T2D) using the common data model. From the de-identified database of three hospitals, 889 patients < 15 years of age diagnosed with T1D or T2D (393 boys, 664 T1D patients) were enrolled. Diagnosis was defined as first exposure to antidiabetic drug at each center. Compared with T2D patients, T1D patients had lower BMIz at diagnosis (− 0.4 ± 1.2 vs. 1.5 ± 1.4, p < 0.001) and 3 months (− 0.1 ± 1.0 vs. 1.5 ± 1.5, p < 0.001), and higher HbA1c levels at diagnosis (10.0 ± 2.6% vs. 9.5 ± 2.7%, p < 0.01). After 3 months, HbA1c levels reached a nadir of 7.6% and 6.5% in T1D and T2D patients, respectively, followed by progressive increases; only 10.4% of T1D and 29.7% of T2D patients achieved the recommended HbA1c target (< 7.0%) at 60 months. T1D patients showed consistent increases in BMIz; T2D patients showed no significant change in BMIz during follow-up. Peri-pubertal girls with T1D had higher HbA1c and BMIz values. Achieving optimal glycemic control and preventing obesity should be emphasized in pediatric diabetes care.